Bacterial factors of mastitis in lactating women and its effect on the physical properties and chemical composition of breast milk - Shuyang, Xu; Qiang, Yu (Cellular and Molecular Biology, 2021)
Mastitis is a complication seen in some breastfeeding mothers and is the most common inflammatory lesion of the breast in breastfeeding mothers. In this complication, breast milk undergoes chemical and physical changes. It can lead to a drop in breastfeeding, weight loss, and, consequently, stunted growth of infants. Bacteria are the main cause of breast inflammation. Therefore, in this study, bacterial factors of mastitis were evaluated in lactating women. Also, their effects were considered on the physical properties and chemical composition of mothers’ breast milk. For this purpose, 210 breastfeeding mothers referred to health centers were randomly selected, and their milk samples were collected. In addition to collecting mothers’ demographic information by a questionnaire, the chemical composition (sugar, protein, and fat) and the physical properties (pH, density, and freezing temperature) of milk were measured. Bacterial evaluations were performed on the milk of these mothers by catalase test, coagulase test, and mannitol salt agar. Data were analyzed by SPSS software, Chi-square, Mann-Whitney U test, and T-test. The results showed that 56 mothers had mastitis, and Staphylococcus aureus and coagulase-negative staphylococci were the main bacteria in the milk of these mastitis mothers. These bacteria caused physical and chemical changes in breast milk so that mothers with Staphylococcus aureus mastitis had less sugar in their milk, and mothers with coagulase-negative staphylococci had less protein in their milk. Therefore, Staphylococcus aureus may reduce milk sugar by consuming milk sugar, and coagulase-negative staphylococci may also target milk protein. But to confirm these results, a larger population of mothers with mastitis is needed. Further studies are also needed to prove this result.